Effect of Nrg1 Repressor on NTH1 Transcription and Molecular Docking of Nrg1 on NTH1 Promoter - Genç, Tülay Turgut; Doğan, Gamze (UI Scholars Hub, 2019)
The amount of intracellular trehalose increases in response to environmental stress in yeast (Saccharomyces cerevisiae). When that stress is terminated, the accumulated trehalose rapidly degrades into glucose rapidly. Synthesis of trehalose is fulfilled by the Trehalose Phosphate Synthase (TPS) enzyme complex, whereas the degradation of trehalose is done by the neutral trehalase enzyme. Under different stress conditions, transcription of the NTH1 gene is activated and Stress Response Elements (STRE) are required for this activation. Nrg1 protein can bind promoters including STRE and PDS elements. Because of the presence of three possible Nrg1 repressor binding sites on the NTH1 promoter, the NTH1 gene may be regulated by the Nrg1 repressor. In order to test this hypothesis, Δnrg1 mutant yeast and its isogenic wild-type yeast strain were used to analyze the transcriptional activation of the NTH1 gene under nitrogen starving conditions. Nth1 transcription of the mutant yeast was seven-fold higher than that of the wild-type under growth conditions, and was not changed during nitrogen starvation. The protein-DNA docking analysis also supported the possibility of Nrg1 binding to the NTH1 promoter. These results revealed that NTH1 gene expression is constitutive in the absence of the Nrg1 repressor protein, hence the transcription of NTH1 is repressed by the Nrg1 protein.